2021
DOI: 10.7759/cureus.13962
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Arthritis of the Ankle Joint Mimicking Pigmented Villonodular Synovitis

Abstract: Osteoarticular tuberculosis (TB) of the ankle joint is rare, and there is a delay in diagnosis in most cases. All patients with the disease complained of swelling and pain in the affected ankle. Ankle TB is a disorder that can be simply misdiagnosed. The delay in diagnosis may range from months up to years. All patients in this series had already been diagnosed with ankle TB by the time they visited our hospital. The current case was reported in a middle-aged male nurse with ankle pain, ulcer, and limited rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There is lack of literature regarding diagnostic tools in TB of small joints, including the midfoot joints. Many authors have reported that in any tubercular osteomyelitis, bone sclerosis or PVNS may be seen in the early course of disease [18] , [19] , [20] . Ruling out other conditions is required, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is lack of literature regarding diagnostic tools in TB of small joints, including the midfoot joints. Many authors have reported that in any tubercular osteomyelitis, bone sclerosis or PVNS may be seen in the early course of disease [18] , [19] , [20] . Ruling out other conditions is required, i.e.…”
Section: Discussionmentioning
confidence: 99%